Urgently Regulating Gacha Microtransactions as Digital Gambling in Indonesian Consumer Protection Theory - Moh. Zidhan Madina; Dolot Alhasni Bakung; Fitran Amrain (Yayasan Cerdas Pedia Indonesia, 2026)
The urgency of microtransaction regulation through the in-game gacha system developed by miHoYo as a form of practice that potentially resembles digital gambling. The gacha system raises legal issues because players spend money to acquire virtual items at random with no certainty of outcome. This research uses normative legal method with legislation, conceptual, and comparative approaches. The results of the study indicate that Indonesia does not yet have specific regulations governing the gacha system, causing a legal vacuum in the protection of digital consumers. Gacha practices also potentially violate the principles of transparency, fairness, and consumers ' right to truthful, clear, and honest information. Therefore, special arrangements are needed that regulate the transparency of opportunities, age restrictions, transaction supervision, and responsibility of digital game business actors.